FIVE YEARS SURVIVAL AND QUALITY OF LIFE AFTER RADICAL NEPHRECTOMY: A DESCRIPTIVE SINGLE CENTER STUDY - Can, Adryansyah; Siregar, Ginanda Putra; Sihombing, Bungaran (Indonesian Urological Association, 2022)
Objective: This study aims to evaluate five years of survival rate, and quality of life of the patient after radical nephrectomy in our center. Material & Methods: This descriptive longitudinal study included thirty patients who were diagnosed as having renal mass in the Urology division H. Adam Malik General Hospital between January 2014 and December 2015. All patients were completely followed-up for 5 years or the patient died during the observation. We used a translated and validated Indonesian written European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Version 3.0 (EORTC QLQ-C30) questionnaire to assess the patient’s quality of life. Results: Overall 5-years survival of kidney tumor patients was 100%, 66.67%, 50%, 8.33%, respectively for stage 1 to 4. We found a sharp decrease in the cumulative survival rate of stage IV group in the first 24 months compared to the first 12 months, from 66.67% to 25%. This pattern of decrease was not found in the other group of stage. Overall, the quality of life of patients has increased in the first three years postoperatively and decreased in the two years afterward. These fluctuations consistently occur in all groups. All of the groups had reached the maximum quality of life at the third year postoperatively. Conclusion: Stage I renal cell carcinoma patient shown the best five-years survival rate and quality of life among others. The quality of life for all groups inclined for the first three years after surgery and decline consistently afterward. These findings are in accordance with many studies that have been published previously.